Financial Liberalization, Property Rights and Growth in A Overlapping Generations Model - Carlotta Berti Ceroni; Giorgio Bellettini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
In this paper we develop an endogenous growth model of open economies, where countries differ with respect to the quality of property rights. Within this context, we analyze two types of reforms. First, we look at growth and welfare effects of removing capital controls, given the degree of property rights protection. Second, we endogenize the quality of property rights and study the political support for a reform aimed at improving it. We show that, in countries where property rights are poorly protected, the liberalization of capital movements, that may or may not foster economic growth in the short-run, eliminates the possibility of sustained physical capital accumulation. Nevertheless, the removal of capital controls may benefit the agents alive at the time of liberalization, leaving a burden for future generations. Ceteris paribus, the political support for a reform of property rights will be stronger in the closed economy than in the open economy.
Keywords: 330